Transcranial Doppler Can Predict Development and Outcome of Sepsis-Associated Encephalopathy in Pediatrics With Severe Sepsis or Septic Shock - Algebaly, HebatAllah; ElSherbini, Seham; Galal, Ahmed; Hamdi, Rania; Baz, Ahmed; Elbeleidy, Ahmed (Frontiers in Pediatrics, 2020)
Background and aim: Sepsis is a common cause of paediatric ICU admission. Sepsis-associated encephalopathy (SAE) may occur due to brain dysfunction in those patients and may be related to impaired cerebral microcirculation. Transcranial Doppler (TCD) can be used to detect this impairment. In this study, we aimed to assess the role of TCD in prediction of SEA and mortality in patients with severe sepsis or septic shock admitted to PICU. Patients and methods: This prospective study included seventy-five children admitted to PICU due to severe sepsis or septic shock. Upon admission, all patients were subjected to careful history taking, thorough clinical examination and standard laboratory work-up. Severity of clinical illness was assessed using the Paediatric Risk of Mortality (PRISM) III score. TCD was performed on the first day of admission after the normalization of systolic blood pressure with or without vasopressors. The primary study outcome was differences in the measurement of TCD in SAE and the secondary outcome was discharge from ICU or mortality. Results: The study comprised forty-five children with SAE and thirty age and sex matched children without SAE. In this study , SAE patients had significantly higher pulsatility index (median (IQR): 1.15 (0.98 - 1.48) versus 1.0 (0.95 – 1.06), p=0.002) and resistive index (median (IQR): 0.68 (0.61 – 0.77) versus 0.62 (0.59 – 0.64), p=0.001) when compared to non-SAE patients. PI and RI showed good performance as predictors of subsequent SAE development (AUC: 0.72 and 0.73 respectively). Non-survivors in SAE patients had significantly higher PRISM III. ROC curve analysis showed good performance of PI and RI as predictors of mortality at the end of follow up.